A 6-Week Badminton-Based Movement Intervention Enhances Fundamental Movement Skills and Physical Fitness in Saudi Boys and Girls - Michael J. Duncan; Abdulrahman AlShabeb; Katie Fitton Davies; Nadia Alshahrani; Yazeed Almasoud (MDPI AG, 2023)
This study examined the short (pre-post) and longer-term (post to 10 weeks post) effects of the Badminton World Federation (BWF) Shuttle Time program on fundamental movement skills (FMS) and physical fitness in Saudi boys and girls. Seventy-six children aged 9-11 years (44 boys, 32 girls; mean ± SD = 10.2 ± 0.9 years) undertook twice weekly Shuttle Time sessions for 6 weeks. Pre, post, and 10 weeks post, FMS was measured using the test of gross motor development 3 and physical fitness was measured via 10 m sprint speed, standing long jump, seated medicine ball throw, and a 6 min walk test (6MWT). There were significant improvements in FMS from pre to post (p = 0.0001) and post to 10-weeks post (p = 0.0001) for both boys and girls. Girls demonstrated a significantly greater magnitude of change in FMS. For 10 m sprint time, seated medicine ball throw, standing long jump, and 6MWT performance, both boys and girls significantly improved from pre-10 weeks post (all p = 0.001). The magnitude of change was greater pre to 10-weeks post for girls for the seated medicine ball throw, but was greater for boys for the standing long jump and 6MWT. In terms of practical applications, the BWF Shuttle Time program is feasible for administration in the Saudi context and is beneficial in developing FMS and fitness for Saudi children aged 8-12 years.